Is this fungus everywhere? Elucidating the genetic structure of populations of the arbuscular mycorrhizal fungus Glomus intraradices - Redecker, Dirk; Boerstler, B.; Thiery, O. (HAL CCSD, 2010)
Format du poster : 21 X 29,7 International audience Arbuscular mycorrhizal fungi (Glomeromycota) are ubiquitous mutualistic associates of plants. Only relatively recently it has become possible to study the population biology of some species of these fungi. The model organism Glomus intraradices has been found across an extremely wide range of habitats and succession stages on different continents using molecular identification approaches. We used regions of the mitochondrially-encoded rDNA as novel molecular markers to resolve the intraspecies structure of G. intraradices and found a high diversity of mitochondrial haplotypes among isolates from all over the world. These markers for the first time also offer to genotype G. intraradices directly within colonized roots. Using this approach, we found a surprisingly high degree of genetic differentiation of G. intraradices among arable sites in Switzerland. Grasslands showed a completely different set of haplotypes compared to arable sites. In addition, haplotypes from geothermal and nonthermal sites in Yellowstone National Park and Iceland were analyzed. These findings will contribute to a better understanding of processes of adaptation and specialization in mutualistic plant/fungus associations. The evolutionary dynamics of the respective mitochondrial gene region was also assessed in other Glomus species, providing evidence for long-term stability or recent horizontal transfer in different introns.